DPYD6 plays an important role in fluoropyrimidine toxicity in addition to DPYD2A and c.2846AT: a comprehensive analysis in 1254 patients - Del Re, Marzia; Cinieri, Saverio; Michelucci, Angela; Salvadori, Stefano; Loupakis, Fotios; Schirripa, Marta; Cremolini, Chiara (The pharmacogenomics journal, 2019)
Dihydropyrimidine dehydrogenase (DPYD) is a highly polymorphic gene and classic deficient variants (i.e., c.1236G>A/HapB3, c.1679T>G, c.1905+1G>A and c.2846A>T) are characterized by impaired enzyme activity and risk of severe adverse drug reactions (ADRs) in patients treated with fluoropyrimidines. The identification of poor metabolizers by pre-emptive DPYD screening may reduce the rate of ADRs but many patients with wild-type genotype for classic variants may still display ADRs. Therefore, the search for additional DPYD polymorphisms associated with ADRs may improve the safety of treatment with fluoropyrimidines. This study included 1254 patients treated with fluoropyrimidine-containing regimens and divided into cohort 1, which included 982 subjects suffering from gastrointestinal G[greater than or equal to]2 and/or hematological G[greater than or equal to]3 ADRs, and cohort 2 (control group), which comprised 272 subjects not requiring dose reduction, delay or discontinuation of treatment. Both groups were screened for DPYD variants c.496A>G, c.1236G>A/HapB3, c.1601G>A (DPYD*4), c.1627A>G (DPYD*5), c.1679T>G (DPYD*13), c.1896T>C, c.1905 + 1G>A (DPYD*2A), c.2194G>A (DPYD*6), and c.2846A>T to assess their association with toxicity. Genetic analysis in the two cohorts were done by Real-Time PCR of DNA extracted from 3 ml of whole blood. DPYD c.496A>G, c.1601G>A, c.1627A>G, c.1896T>C, and c.2194G>A variants were found in both cohort 1 and 2, while c.1905+1G>A and c.2846A>T were present only in cohort 1. DPYD c.1679T>G and c.1236G>A/HapB3 were not found. Univariate analysis allowed the selection of c.1905+1G>A, c.2194G>A and c.2846A>T alleles as significantly associated with gastrointestinal and hematological ADRs (p < 0.05), while the c.496A>G variant showed a positive trend of association with neutropenia (p = 0.06). In conclusion, c.2194G>A is associated with clinically-relevant ADRs in addition to the already known c.1905+1G>A and c.2846A>T variants and should be evaluated pre-emptively to reduce the risk of fluoropyrimidine-associated ADRs.